2016
DOI: 10.1080/10803548.2015.1078046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of occupational health nursing practice on musculoskeletal pains among hospital nursing staff in South Korea

Abstract: Administration strategies for nurses to adjust work-time within 46 h/week should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…However, our study results showed that nurses working in excess of three hours of overtime per week did have a significantly higher level of near-miss error experiences, aligning with certain aspects of earlier research [ 25 ] that indicated an increase in medication errors when overtime exceeded four hours. Previous study reported that nurses’ long work hours related with job stress [ 26 ]. Since nurses’ job stress was a significant factor influencing the occurrence of near-miss errors, long work hours might be a potential factor influencing the occurrence of near-miss errors.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study results showed that nurses working in excess of three hours of overtime per week did have a significantly higher level of near-miss error experiences, aligning with certain aspects of earlier research [ 25 ] that indicated an increase in medication errors when overtime exceeded four hours. Previous study reported that nurses’ long work hours related with job stress [ 26 ]. Since nurses’ job stress was a significant factor influencing the occurrence of near-miss errors, long work hours might be a potential factor influencing the occurrence of near-miss errors.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the healthcare sector, ML has been utilized for targeting specific hazards. For instance, ANNs have been used to approach the burnout process [27] and statistical analysis has been employed to identify factors of musculoskeletal disorders in nursing staff [28] and to improve the management of indoor air quality in the hospital workplace [29]. Correlation methods have been used to assess the Quality of Work-Life (QWL) for the nursing profession in China [30].…”
Section: Imentioning
confidence: 99%
“…17 Além disso, há associação entre a jornada semanal de trabalho e a ocorrência de dores nos ombros e pescoço. 18 Portanto, verificou-se que precarização no processo de trabalho da enfermagem repercute diretamente na assistência prestada e na qualidade do cuidado, influenciando negativamente na saúde dos trabalhadores que participaram da pesquisa.…”
Section: Repercussões Da Precarização Na Saúde Do Trabalhadorunclassified